Synthesis of surface water hydrology - Neil, C. R. (1979)
The drainage system of the study area consists of a number of rivers draining from the west and from the east into the Athabasca River north of Fort McMurray, as well as a few rivers which join the Athabasca near Fort McMurray and drain areas to the south and east. Runoff from within the study area itself contributes less than 10% of the average flow in the Athabasca River at the northern boundary of the study area. Roughly 60% of annual runoff occurs in the 4-month period April through July. Runoff represents on the average only about 20% of the precipitation that falls on the area, the remainder being returned to the atmosphere by evaporation and transpiration. Although snowfall constitutes only about 30% of precipitation, its proportional contribution to runoff is generally much greater. On the east slopes of the Birch Mountains, runoff from rainfall appears to be remarkably small. Although the spatial variability of average runoff over the study area is not well defined by available streamflow data, it is clear that there is a wide range, from perhaps 30 mm per year on the east slopes of the Birch Mountains to 160 mm per year south of Fort McMurray. These differences are due only in part to differences in precipitation, and must reflect to a greater degree differences in physiographic features that affect evapotranspiration. Year to year variations in runoff are quite high for many of the rivers draining the study area. For example, annual flow volumes in the MacKay River have varied fourfold in only five years of records. In the Athabasca River, annual variations are much less, covering approximately a twofold range in a 20-year period. Few data are available to permit analysis of interactions between surface water and groundwater. Observational well data indicate substantial recharge of groundwater following snowmelt and rainstorms. There are indications that on the east slopes of the Birch Mountains, substantial subsurface flow to the Athabasca River may account in part for the low measurements of runoff ...